Esophageal metastasis from primary colon adenocarcinoma: presentation of an unusual clinical case - Puentes Manosalva, Fabian Eduardo (2025)
Colorectal cancer is one of the tumors with the highest incidence and mortality worldwide.Despite being considered a preventable pathology due to the modifiable risk factors andthe appropriate use of screening strategies, there are currently still important barriers withrespect to access to health services and adoption of the screening tests, which is reflectedin a non-negligible percentage of patients with the presence of metastasis or unresectabledisease at the time of diagnosis. The most frequent sites of metastasis in colorectal cancerare widely known, however, these patients may present metastatic lesions to unusual sitesthat have not been frequently reported in the literature. We present the unusual case of apatient with colon cancer with metastasis to the esophagus.